INTEGRATION OF SHARIA PRINCIPLES AND GREEN ECONOMY BUSINESS TRENDS FOR BUSINESS SUSTAINABILITY - Azzahro, Za’imah (Penelitian dan Pengembangan Ilmu, 2025)
The global environmental crisis and climate change have created an urgent need for a sustainable economic model. This model not only focuses on growth, but also pays serious attention to the preservation of nature. Green economy emerges as an alternative solution, with an emphasis on resource efficiency and social justice. Meanwhile, the principles of Islamic economics emphasize ethical values such as justice, balance and sustainability, which are highly relevant in supporting the concept of a green economy. The research aims to examine the relationship ang potential integration between the principles of sharia economics and green economy, as well as analyze the opportunities and challenges of its implementation in Indonesia, which is a Muslim-majority country. The method used in this research literature study, by analyzing various scientific references, academic journals, and policy documents related to the theme of Islamic economics and environmentally sustainable development. The result shows that there is great potential to integrate Islamic economics and green economy, especially through instruments such as green sukuk and productive zakat, However, the implementation still faces a number of obstacles, including limited regulations, low public literacy, and lack of innovation in environmentally-focused Islamic financial products.